Differences in pronotum shape in Phlaeothripinae thrips (Thysanoptera) of quarantine importance - Allan H. Smith-Pardo (Academia Biology)
A geometric morphometrics (GMM) approach was applied to explore if pronotum shape can be used for genus-level identification in adult Phlaeothripinae. To do that, a multitude of digital images and illustrations of different genera of phytophagous phlaeothripine thrips were examined to compare their pronotum shape for genera that contain more than 20 species, which are known to feed on plants, as well as those that have been intercepted at U.S. ports of entry coming from other countries. Statistically significant differences in the pronotum shape were found between most of the examined genera, making GMM a viable tool for genus-level identification of adults of most species-rich, phytophagous genera of Phlaeothripinae.